Progestagens and progesterone receptor modulation: effects on the brain, mood, stress, and cognition in females - Bencker, Celine; Gschwandtner, Laura; Nayman, Sibel; Grikšienė, Ramunė; Nguyen, Billie; Nater, Urs M.; Guennoun, Rachida; Sundström-Poromaa, Inger; Pletzer, Belinda; Bixo, Marie; Comasco, Erika (Frontiers in neuroendocrinology, 2025)
Progesterone is a highly lipophilic gonadal hormone that can influence behavior and mental health through its receptors in the brain. Fluctuations in progesterone levels across critical periods of a females life are associated with increased susceptibility to mental conditions. This review highlights the effects of progestagens, including progesterone and synthetic progestins, on the brain, mood, stress, and cognition in females. The primary focus is on experimental pharmacological research that teases out the distinct effects of progestagens from those of estrogens. Additionally, the key literature on puberty, the menstrual cycle, pregnancy, perimenopause, hormonal contraceptives, and menopausal hormone therapy is reviewed, although conclusions are limited by the nested effects of progestagens and estrogens. Single study-findings suggest an influence of progesterone on amygdala reactivity related to processing of emotional stimuli and memory. In patients with premenstrual dysphoric disorder, progesterone receptor modulation improves premenstrual mood symptoms and potentially enhances fronto-cingulate control over emotion processing. The interaction between progestagens and the systems involved in the regulation of stress seems to influence subjective experiences of mood and stress. Sparse studies investigating the effects of progestin-only contraceptives suggest effects of progestagens on the brain, mood, and stress. Progesterone and progestins used for contraception can influence neural processes as myelination and neuroprotection, exerting protective effects against stroke. Concerning menopausal hormonal therapy, the effects of progestins are largely unknown. Levels of progesterone as well as type, administration route, timing, dose regimen, metabolism, and intracellular activity of progestins in hormonal contraceptives and menopausal hormonal therapy are factors whose effects remain to be elucidated. Altogether, current knowledge highlights the potential role of progestagens in females health but also calls for well-designed pharmaco-behavioral studies disentangling the effects of progestagens from those of estrogens.